Assessment of the impact of the London Olympics 2012 on selected non-genitourinary medicine clinic sexual health services. (April 2015) - Hartley, A; Foster, R; Brook, MG; Cassell, JA; Mercer, CH; Coyne, K; Hughes, G; Crook, P
With minimal information on sexual health provision during mass-gathering events, our aim was to describe the use of sexual health, contraceptive, sex worker and sexual assault services during the London 2012 Olympics. We analysed data from five sources. One contraceptive service provider reported a 10% increase in attendance during the main Games, while emergency contraception prescriptions rose during the main Olympics, compared to the week before, but were similar or lower than at the beginning and end of the summer period. A health telephone advice line reported a 16% fall in sexual health-related calls during the main Olympics, but a 33% increase subsequently. London sexual assault referral centres reported that 1.8% of sexual assaults were Olympics-linked. A service for sex workers reported that 16% started working in the sex industry and 7% moved to London to work during the Olympics. Fifty-eight per cent and 45% of sex workers reported fewer clients and an increase in police crack-downs, respectively. Our results show a change in activity across these services during the 2012 summer, which may be associated with the Olympics. Our data are a guide to other services when anticipating changes in service activity and planning staffing for mass-gathering events.